2011
DOI: 10.1007/s00211-011-0379-y
|View full text |Cite
|
Sign up to set email alerts
|

Multigrid algorithms for symmetric discontinuous Galerkin methods on graded meshes

Abstract: We study a class of symmetric discontinuous Galerkin methods on graded meshes. Optimal order error estimates are derived in both the energy norm and the L 2 norm, and we establish the uniform convergence of V -cycle, F-cycle and W -cycle multigrid algorithms for the resulting discrete problems. Numerical results that confirm the theoretical results are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…In 2003 Gopalakrishnan and Kanschat [6] analyzed a V-cycle preconditioner for diffusion and advectiondiffusion problems. Multigrid algorithms for dG discretizations of elliptic problems were considered by Brenner et al [7], who proved uniform convergence with respect to the number of levels for F-,V-and W-cycle on graded meshes, and Antonietti et al [8], who provided similar results for W-cycle h-,p-and hp-multigrid. While the previous works employed h-refined mesh sequences, Prill et al [9] considered smoothed aggregation to build coarse problems for h-multigrid dG solvers.…”
Section: Introductionmentioning
confidence: 98%
“…In 2003 Gopalakrishnan and Kanschat [6] analyzed a V-cycle preconditioner for diffusion and advectiondiffusion problems. Multigrid algorithms for dG discretizations of elliptic problems were considered by Brenner et al [7], who proved uniform convergence with respect to the number of levels for F-,V-and W-cycle on graded meshes, and Antonietti et al [8], who provided similar results for W-cycle h-,p-and hp-multigrid. While the previous works employed h-refined mesh sequences, Prill et al [9] considered smoothed aggregation to build coarse problems for h-multigrid dG solvers.…”
Section: Introductionmentioning
confidence: 98%
“…In [40,41] a Fourier analysis of a multigrid solver for a class of DG discretizations is performed, focusing on the performance of several relaxation methods, while in [53] the analysis concerns convection-diffusion equations in the convection-dominated regime. Other contributions can be found for low-order DG approximations: in [22] it is shown that V-cycle, F-cycle and W-cycle multigrid algorithms converge uniformly with respect to all grid levels, with further extensions to an over-penalized method in [19] and graded meshes in [18,17]. At the best of our knowledge, no theoretical results in the framework of p-and hp-DG methods are available, even though p-multigrid solvers are widely used in practical applications, cf.…”
mentioning
confidence: 99%
“…This came after an additive multigrid convergence theory was developed in for conforming finite element methods that establishes the decay rate of the contraction numbers and completes the generalization of . The results in have since been extended to other nonconforming methods and DG methods .…”
Section: The Poisson Problemmentioning
confidence: 97%